2013
DOI: 10.4161/epi.26346
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation assay reveals novel candidate biomarker genes in cervical cancer

Abstract: The oncogenic human papilloma viruses (HPVs) are associated with precancerous cervical lesions and development of cervical cancer. The DNA methylation signatures of the host genome in normal, precancerous and cervical cancer tissue may indicate tissue-specific perturbation in carcinogenesis. The aim of this study was to identify new candidate genes that are differentially methylated in squamous cell carcinoma compared with DNA samples from cervical intraepithelial neoplasia grade 3 (CIN3) and normal cervical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 75 publications
(57 reference statements)
4
77
0
Order By: Relevance
“…This included: 20 cervical tissues from GSE46306 [31]; 17 and 5 saliva samples from GSE39560 and GSE48472 respectively [32,33]; 5 and 6 venous blood samples from GSE48472 and GSE35069 respectively [33,34]; and 8 sperm samples from GSE47627 [35]. For each CpG locus in the Infinium HumanMethylation450 BeadChip Kit, mean and standard deviation of the beta-values (the calibration ratio of methylation) for each biofluid or tissue were calculated using Microsoft Office Excel 2007.…”
Section: Selection Of Candidate Cpg Locimentioning
confidence: 99%
“…This included: 20 cervical tissues from GSE46306 [31]; 17 and 5 saliva samples from GSE39560 and GSE48472 respectively [32,33]; 5 and 6 venous blood samples from GSE48472 and GSE35069 respectively [33,34]; and 8 sperm samples from GSE47627 [35]. For each CpG locus in the Infinium HumanMethylation450 BeadChip Kit, mean and standard deviation of the beta-values (the calibration ratio of methylation) for each biofluid or tissue were calculated using Microsoft Office Excel 2007.…”
Section: Selection Of Candidate Cpg Locimentioning
confidence: 99%
“…Accordingly, it is well established that IDH1/IDH2 mutations will induce a glioma CpG island hypermethylator phenotype (G-CIMP) and this phenotype is preserved throughout glioma progression [6,10]. The role of methylation changes have been associated with tumor progression in different types of cancer [27][28][29]. In GBM, the presence of hypermethylation of tumor suppressors (RB1, EMP3, RASSF1A and BLU), cell cycle regulators (CDKN2A), DNA repair genes (MGMT, MLH1), and genes involved in tumor invasion and apoptosis (DAPK, TIMP3 and CDH1) is frequent [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF582 was found to be hypermethylated in HSIL lesions and cervical cancer samples, after validation in an independent cohort. 38 These studies have demonstrated that global DNA methylation assays, like MeDIP-arrays, are powerful tools for the genomewide study of methylated genes in cervical cancer. The fact that we did not find any correlation between the candidate genes reported by these studies and the ones we are reporting may be due to differences in sample source, sample collection, microarray kinetics, bioinformatics pipelines, genetic and/or cultural factors, all of which can affect the end results of these complex experiments.…”
Section: Discussionmentioning
confidence: 99%